National Statistical Management System: Opportunities, Challenges and Future Steps - Thapa, Manish (Nepal Public Policy Review, 2021)
Globally, countries adopt either centralized or decentralized statistical management system. With over 60 years of history, Nepal has been practicing decentralized statistical management system where various government agencies alongside non-government and private agencies manage statistics based on their needs and requirements. Statistics Act 1958 set the foundation for statistical management system, that is in operational stage as of 2021. This paper sets an objective of reviewing the legal instruments associated with statistical management system and explores the opportunities and challenges of integrated statistical management system. Paper adopts systematic literature review method to search, sort and filter the relevant literature associated with opportunities and challenges of statistical management systems and/or practices. The adoption of statistical management system among countries were found to be varied (centralized/decentralized) based on the countries’ needs, interests, capacity to set-up infrastructures. Hence the paper recommends updating the statistics related legal instruments and emphasizes the establishment of single institution. Based on which, country can adopt the principle and modality of either centralized or integrated statistical management system based on its needs and interests. After identifying the complexity, privacy, confidentiality, safety and security associated with integrated statistical management system, the paper suggests laying out a foundational framework for a strong and effective system. Afterwards possible concerns could be addressed through updated statistical acts and rules.